Field Identification of Citrus Canker Symptoms and Decontamination Procedures - Mongi Zekri; Megan M. Dewdney; Jamie D. Yates; Pamela Roberts (EDIS)
Citrus canker, caused by the bacterial pathogen Xanthomonas citri subsp. citri, is a serious disease of citrus. The disease causes necrotic dieback, general tree decline, premature fruit drop, and fruit blemishes. Severely infected trees become weak, unproductive, and unprofitable. Learn how to identify citrus canker and proper procedures for decontamination with this 5-page fact sheet written by Mongi Zekri, Megan Dewdney, Jamie Yates, and Pamela Roberts, and published by the UF Department of Plant Pathology, July 2011.